A Mysterious Case of a Breast Lump in a Woman From the Philippines. Issue 1 (January 2018) - Rennert-May, Elissa; Dixit, Devika
Abstract : Abstract: We present the case of a 74-year-old woman who recently emigrated from the Philippines to Canada, with an unusual etiology for her breast lump. Based on review of breast histopathology by a pathologist, as well as parasitology specialist and clinical history, the causative organism of this breast lump was Schistosoma japonicum . This is an uncommon manifestation of schistosomiasis, which causes more than 40 million clinical infections annually. Abstract : Schistosomiasis is a common cause of tropical infections but it can present in unusual ways. In this case, a woman from the Philippines presented with a breast lump thought to likely be cancerous. After repeated biopsies, the presence of calcified egg shells consistent with Schistosoma species was discovered. This case highlights the importance of taking into consideration travel and immigration history.